2007
DOI: 10.1021/jo070443m
|View full text |Cite
|
Sign up to set email alerts
|

A β-Keto Ester as a Novel, Efficient, and Versatile Ligand for Copper(I)-Catalyzed C−N, C−O, and C−S Coupling Reactions

Abstract: Employing ethyl 2-oxocyclohexanecarboxylate as a novel, efficient, and versatile ligand, the copper-catalyzed coupling reactions of various N/O/S nucleophilic reagents with aryl halides could be successfully carried out under mild conditions. A variety of products including N-arylamides, N-arylimidazoles, aryl ethers, and aryl thioethers were synthesized in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(144 citation statements)
references
References 12 publications
2
131
0
11
Order By: Relevance
“…All these complexes appear to exist in an ionic form in the solid state and in the polar solvents that are often used for copper-catalyzed coupling of phenoxides. [24][25][26][27][28][29][30] This ionic form contains two Cu I sites, one bound by two chelating, dative ligands, and one by two phenoxides. In contrast to prior proposals of the reaction of anionic phenoxide complexes of copper, the isolated anion containing an ammonium counter-ion did not react with iodoarenes in high yields.…”
Section: The Reaction Of O-(allyloxy)iodobenzene With the P-cresolatementioning
confidence: 99%
“…All these complexes appear to exist in an ionic form in the solid state and in the polar solvents that are often used for copper-catalyzed coupling of phenoxides. [24][25][26][27][28][29][30] This ionic form contains two Cu I sites, one bound by two chelating, dative ligands, and one by two phenoxides. In contrast to prior proposals of the reaction of anionic phenoxide complexes of copper, the isolated anion containing an ammonium counter-ion did not react with iodoarenes in high yields.…”
Section: The Reaction Of O-(allyloxy)iodobenzene With the P-cresolatementioning
confidence: 99%
“…Melting points (mp) were obtained on a B-540 Büchi melting-point apparatus and are uncorrected. 1 H NMR (400 MHz) and 13 C NMR (100 MHz) data were recorded on a DPX-400 instrument with CDCl 3 or DMSO-d 6 as solvents and tetramethylsilane (TMS) as the internal standard. Chemical shifts are given in ppm and spin-spin coupling constants, J, are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, great attention has been paid to the improvement of Ullmann-type couplings, and significant progress has been made. Recently, many ligands have been introduced to promote copper-catalyzed C-N coupling efficiently, including diamines, 3 1,10-phenanthroline, 4 amino acids, 5 N.N-diethylsalicylamide, 6 ethylene glycol, 7 8-hydroxyquinoline, 8 an aminoarenethiol, 9 1,1,1-tris(hydroxymethyl)ethane, 10 2-aminopyrimidine-4,6-diol, 11 1,1'-binaphthyl-2,2'-diol, 12 ethyl 2-oxocyclohexanecarboxylate, 13 and so on. These Cu/ligand catalyzed reactions are significantly superior to the conventional Pdmediated reactions with low cost, mild reaction conditions and good compatibility with functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The results clearly revealed that an electron-withdrawing group in the aryl bromides favored the coupling reactions (Table 4, entries 24-29 vs 1-4, 10), however an electron-releasing group in the aryl bromides went against the coupling reactions. For example 4-methylbromobenzene could be coupled with phenol to give the products in 59-85% yields (Table 4, entries [11][12][13][14][15][16][17][18], yet aryl bromides with electron-withdrawing substituents, e.g. 2-acetylphenyl bromide, afforded the corresponding products in 86-95% yields (Table 4, entries 24-25, 27-28) with the exception of 4-cyanophenol, which led to a low yield (56%) for the coupling reaction (Table 4, entry 29).…”
Section: Notesmentioning
confidence: 99%